Electron Pitch Angle Distributions in Compressional Pc5 Waves by THEMIS‐A Observations. Issue 22 (16th November 2021) - Ma, X.; Tian, A. M.; Shi, Q. Q.; Bai, S. C.; Yao, S. T.; Shen, X. C.; Sun, W. J.; Guo, R. L.; Nowada, M.; Degeling, A. W.; Liu, J.; Li, L.; et al.
Abstract: Although compressional Pc5 waves are well known in the energy conversion and regulation of charged particles in the magnetosphere, the detailed features of associated electron pitch angle distributions (ePADs) are poorly understood. Based on Time History of Events and Macroscale Interactions during Substorms (THEMIS) observations from 2010 to 2016, ePADs in the magnetic decreases (troughs) of compressional Pc5 waves are classified into three types: cigar, butterfly, and pancake. They are found in the electrons with respective energy ranges of 100–1, 000 eV (larger than 10 keV), 1–10 keV (larger than 1 keV), and 6–30 keV (100 eV–10 keV) in (non)whistler‐type compressional Pc5 waves, that is, cases where whistler‐mode waves are present (absent) in the magnetic troughs. These statistical ePAD features observed in the whistler‐ and nonwhistler‐type waves are suggested to be associated with the Landau resonance of whistler‐mode waves and drift‐shell splitting effect. Plain Language Summary: Ultralow frequency (ULF) waves play a significant role in modifying the charged particles in the magnetosphere. In compressional Pc5 waves, each magnetic trough can be considered a mirror‐like structure. Therefore, such waves can significantly modulate charged particles. Studying the ePADs in compressional Pc5 waves is crucial for understanding the dynamic behaviors of electrons. Using THEMIS‐A data, we present a statistical study to investigate ePADs in compressional Pc5 waves. ePADs are mainly observed in three types: cigar, butterfly, and pancake. Each of the ePADs shows a different energy dependence in two types of compressional waves. The two types of events are defined based on the presence or absence of whistler‐mode waves in the magnetic troughs of compressional Pc5 waves. The statistical results suggest that the ePADs in nonwhistler‐type compressional waves are affected by the background ePADs. For whistler‐type compressional waves, whistler wave‐particle interactions might be important, suggesting a cross‐scale coupling of the energy transport in compressional Pc5 waves. Key Points: Cigar, butterfly, and pancake electron pitch angle distributions are found in the magnetic troughs of compressional Pc5 waves Electron pitch angle distributions show different energy dependences in whistler‐ and nonwhistler‐type compressional Pc5 waves Electron pitch angle distribution features in compressional waves could be related to Landau resonance and drift shell splitting